Exploring Consumer Behavior in the Private Aviation Charter Industry: A Comprehensive Study - Rhazaoui, Chaima (Global journal of Business and Integral Security, 2024)
Consumer behavior in the private aircraft charter market is a complicated and changing phenomenon driven by a variety of factors. This study investigates the factors that influence consumers’ preferences and decision-making processes while seeking private aircraft charter services. The study uses a mixed-methods approach, integrating surveys, interviews, and an existing literature review, to explore factors influencing consumer choices, preferences, and decision-making processes within the realm of private aviation charter services. The findings show that consumers in the private aircraft charter business favor perceived value characteristics such as cost-effectiveness and time efficiency over the convenience of private flights. Safety perceptions and service quality are also important issues, with customers wanting professionalism, dependability, and individualized experiences. The study emphasizes the need of understanding private aviation users’ different tastes and objectives to successfully personalize goods and services and emphasizes the importance for private aviation operators to promote safety, professionalism, and individualized experiences to increase customer satisfaction and loyalty. This research has implications for industry executives, policymakers, and marketing experts, providing actionable insights for improving marketing tactics, service offerings, and operational procedures in the aviation industry.